Thiamine deficiency - Beriberi – A forgotten disease - Hassan, Mahmuda; Rahman, Hamidur; Yasmeen, BH Nazma; Mukti, Afsana; Haque, Hakimul; Khan, Masuma; Begum, Marium; Roy, Sudipta; Ahmed, Taslim Uddin; Ahmed, Ashraf Uddin; et al. (Northern International Medical College Journal, 2018)
Thiamine (vitamin B1) was the first B vitamin which has been identified. It serves as a cofactor for several enzymes involved in energy metabolism. The thiamine-dependent enzymes are important for the biosynthesis of neurotransmitters and for the production of reducing substances used in oxidant stress defenses, as well as for the synthesis of pentose used as nucleic acid precursors. Thiamine also plays a central role in cerebral metabolism. There are 2 major manifestations of thiamine deficiency(TD): cardiovascular disease (wet beriberi) and nervous system disease (dry beriberi and Wernicke–Korsakoff syndrome). In wet beriberi, cardiomyopathy with edema and lactic acidosis and in dry beriberi, peripheral neuropathy occurs. Manifestations of Wernicke–Korsakoff syndrome, consist of nystagmus, ophthalmoplegia and ataxia evolving into confusion, retrograde amnesia, cognitive impairment and confabulation. Thiamine deficiency is now very rare in developed countries, but still common in South East Asia specially in developing countries like Bangladesh. It is an important public health problem with potentially fatal consequences. Now a days highly polished rice (Minicut rice) is a popular staple food and other primary dietary sources of thiamine are in short supply. In wet beriberi myocardial disease is prominent which causes a high cardiac output with peripheral vasodilation and warm extremities. Before heart failure, tachycardia, a wide pulse pressure, sweating, warm skin and lactic acidosis develop leading to salt and water retention by the kidneys. The resulting fluid overload leads to edema of the dependent extremities. If it is left untreated the severity of potential outcome will be increased even up to death. Therefore, makes it essential for physician, cardiologists and Paediatrician to have an understanding of this condition and its optimal treatment. Patients on a strict thiamine-deficient diet display a state of severe depletion within 18 days. The most common cause of thiamine deficiency in affluent countries is either alcoholism or malnutrition in nonalcoholic patients especially in children. Treatment by thiamine supplementation is beneficial for diagnostic and therapeutic purposes. Northern International Medical College Journal Vol.10(1) Jul 2018: 351-354